Brain functions after sports-related concussion: Insights from event-related potentials and functional MRI - Gosselin, N.; Saluja, R. S.; Chen, J.-C.; Bottari, C.; Johnston, K.; Ptito, A. (The Physician and Sportsmedicine, 2010)
The high incidence of concussions in contact sports and their impact on brain functions are a major cause for concern. To improve our understanding of brain functioning after sports-related concussion, advanced functional assessment techniques, namely event-related potentials (ERPs) and functional magnetic resonance imaging (fMRI), have been recently used in research studies. Contrary to neuropsychological tests that measure verbal and/or motor responses, ERPs and fMRI assess the neural activities associated with cognitive/behavioral demands, and thus provide access to better comprehension of brain functioning. In fact, ERPs have excellent temporal resolution, and fMRI identifies the involved structures during a task. This article describes ERP and fMRI techniques and reviews the results obtained with these tools in sports-related concussion. Although these techniques are not yet readily available, they offer a unique clinical approach, particularly for complex cases (ie, athletes with multiple concussions, chronic symptoms) and objective measures that provide valuable information to guide management and return-to-play decision making.